Light-driven drag and drop assembly of micron-scale bilayer networks for synthetic biology - Friddin,MS; Bolognesi,G; Elani,Y; Brooks,NJ; Law,RV; Seddon,JM; Neil,MAA; Ces,O (2016)
We have developed a new method to assemble single- or multi-layered networks of droplet interface bilayers (DIBs) from cell-sized droplets using a single beam optical trap (optical tweezers). The novelty of our approach is the ability to directly trap the microdroplets with the laser and manipulate them in 3D to construct DIB networks of user-defined architectures. Our method does not require a complex optical setup, is versatile, contactless, benefits from both high spatial and temporal resolution, and could set a new paradigm for the assembly of smart, synthetic biosystems.